Can probiotics win the battle against environmental endocrine disruptors? - Sevim, Çiğdem; Kara, Mehtap (Archives of Pharmacy, 2021)
Compounds that have negative effects on the endocrine system are called endocrine-disrupting compounds (EDCs). There are several different types of compounds, with several different usage areas in the environment, which can be classified as EDCs. These chemicals have a wide range of negative health effects in organisms, depending on their target hormone system. EDCs are among the most popular topics of scientific research, as they are widely used and organisms are frequently exposed to these chemicals. There are various exposure routes for EDCs, such as oral, inhalation and dermal exposure. Parabens, phenolic compounds, phthalates, and pesticides are the most common EDCs. Nowadays, intestinal microorganism distribution, probiotics, and food supplements that regulate these microorganisms and their protective effects against various harmful chemicals attract attention. For this reason, many studies have been carried out in this field and certain diet schemes have been created according to the results of these studies. In fact, probiotics are preferred in order to reduce and eliminate the negative effects of harmful chemicals and to ensure that the organism reacts strongly in these conditions. In this review, we will focus on EDCs, their health effects and positive effects of probiotics on EDCs exposure conditions.